Proceedings of the 2013 International Conference on Intelligent User Interfaces 2013
DOI: 10.1145/2449396.2449403
|View full text |Cite
|
Sign up to set email alerts
|

Recommending targeted strangers from whom to solicit information on social media

Abstract: We present an intelligent, crowd-powered information collection system that automatically identifies and asks targeted strangers on Twitter for desired information (e.g., current wait time at a nightclub). Our work includes three parts. First, we identify a set of features that characterize one's willingness and readiness to respond based on their exhibited social behavior, including the content of their tweets and social interaction patterns. Second, we use the identified features to build a statistical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Jalal et al [150] built a crowd-source 'qCrowd' which automatically selects strangers in Twitter to get response for the information requested, proving both recommendation algorithm and prediction model. Twitter is used to analyze the real time traffic-related events.…”
Section: International Journal Of Applied Information Systems (Ijais)mentioning
confidence: 99%
“…Jalal et al [150] built a crowd-source 'qCrowd' which automatically selects strangers in Twitter to get response for the information requested, proving both recommendation algorithm and prediction model. Twitter is used to analyze the real time traffic-related events.…”
Section: International Journal Of Applied Information Systems (Ijais)mentioning
confidence: 99%
“…For deriving personality traits Linguist Inquiry and Word Count (LIWC) [20] had been used frequently. References [20][21][22][23][24][25][26][27][28][29] have shown that lexicons used by people can be used for understanding their personal values and how to use these traits for a recommendation. Though all these approaches have been used extensively in analyzing personality traits, these also have shortcomings of predefined word category correlation.…”
Section: Related Workmentioning
confidence: 99%
“…In this perspective, a common approach early developed in community Q&A services [24,22] and in other popular social networks, such as Facebook and Twitter [17,25], consists in routing the questions to a list of the top-k appropriate users. The users' appropriateness is generally estimated using a set of features from the questions, the users themselves and their relations with the questioner.…”
Section: Introductionmentioning
confidence: 99%